2019
DOI: 10.3389/fneur.2019.00929
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Psychoeducation and Cognitive Rehabilitation After Mild Traumatic Brain Injury for Preventing Post-concussional Syndrome in Individuals With High Risk of Poor Prognosis: A Randomized Clinical Trial

Abstract: Unfavorable outcomes (UO) occur in 15–20% of patients with mild traumatic brain injury (mTBI). Early identification of patients at risk of UO is crucial for suitable management to be initiated, increasing the chances of full recovery. We previously developed a prognostic tool for early identification (8–21 days after the injury) of patients likely to develop UO. Patients whose initial risk factors indicate UO are at risk of developing post-concussion syndrome (PCS). In the present study, we examined the benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
1
20
0
1
Order By: Relevance
“…Patient education on the presence of these symptoms, given as instructions at discharge from the ED, can also facilitate better outcome. A recent study on unfavorable outcomes in patients with mild TBI showed that early multidimensional management involving psychoeducation and cognitive rehabilitation considerably improves the outcome of these patients [ 37 ]. Future research could further explore the patterns of cognitive, somatic and emotional symptoms to provide specific interventions to reduce post-concussion symptoms and therewith optimize recovery of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Patient education on the presence of these symptoms, given as instructions at discharge from the ED, can also facilitate better outcome. A recent study on unfavorable outcomes in patients with mild TBI showed that early multidimensional management involving psychoeducation and cognitive rehabilitation considerably improves the outcome of these patients [ 37 ]. Future research could further explore the patterns of cognitive, somatic and emotional symptoms to provide specific interventions to reduce post-concussion symptoms and therewith optimize recovery of injury.…”
Section: Discussionmentioning
confidence: 99%
“… 42 , 43 Furthermore, 1 relevant RCT 44 was identified in a systematic review for manual treatment of neck and back. A total of 19 individual RCTs 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 comprising 2007 participants (1064 women [53.0%]; 943 men [47.0%]) were identified for 6 of the clinical questions. Nine 43 , 45 , 46 , 47 , 49 , 52 , 53 , 55 , 60 of these included a minority of adolescents in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…Caplain et al, 54 Elgmark-Andersson et a,l 55 Kjeldgaard et a,l 56 Potter et al, 57 Rytter et al, 42 Silverberg et al, 58 Thastum et al, 43 Tiersky et al, 59 and Vikane et al 60 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of objective gains in cognition has been lacking since these publications. Caplain et al (2019) investigated the use of a "multidimensional management" approach, which used psychoeducation plus cognitive rehabilitation for participants at high risk of developing pPCS following mTBI. Results showed that 94% of treated participants did not have pPCS 6 months after injury, whereas 52% of the control patients had pPCS.…”
Section: Current Treatmentsmentioning
confidence: 99%